Diabetic foot disease: "The Times They are A Changin' ". (16th March 2020) - Bus, Sicco A.; van Netten, Jaap J.; Monteiro‐Soares, Matilde; Lipsky, Benjamin A.; Schaper, Nicolaas C.
Abstract: Diabetic foot disease greatly impacts both affected patients and society, but remains the "Cinderella" of diabetes‐related complications. However, recent progress in research and guideline development have led to increased awareness of the problem and improved clinical outcomes. Thus, it is time for a shift in global perception of this increasingly prevalent problem. In this special issue, we present 7 up‐to‐date clinical guidelines and 10 systematic reviews developed by the International Working Group on the Diabetic Foot, together with 17 informative and stimulating related papers. These guidelines offer new recommendations on ulcer classification, diagnosis of infection severity, and vascular assessment, to assist in ulcer risk stratification, diagnosis and interdisciplinary communication. Key developments include providing guidance on methodological assessment of research papers; expanding the evidence base for ulcer treatment by the use of wound products and offloading treatment and suggestions for improving ulcer prevention through technological advances in patient monitoring of risk factors and footwear. The 17 invited papers discuss related topics ranging from stem cell research to patient psychology and describe the way forward in diabetic foot care. While there is much more to learn, the new knowledge of underlying pathways, advancements in diagnosis, treatment and prevention presented in this supplement should help improve outcomes and reduce the great and growing burden of diabetic foot disease.